Determining The Etiological Factors in Pleural Fluid by Crp, Albumin And Procalcitonin Levels: New markers in pleural fluid identification - Celikhisar, Hakan; Ilkhan, Gulay Dasdemir (Jour Med Resh and Health Sci, 2020)
Abstract Aim: The Light criteria with a specificity of 72% and a sensitivity of 100% have led to further research into the detection of more specific diagnostic methods for transudate exudate separation. In this study, we aimed to evaluate whether pleural fluid and serum CRP, procalcitonin, on the other hand CRP / Albumin and Procalcitonin / Albumin ratios may be suggested as an alternative to Light criteria in the differential diagnosis of pleural effusions. Material and Method: In this study, the pleural effusions of 121 patients who were aged ?18?years were evaluated. The study was planned as a prospective cohort type study. Results: Effusions were divided into two sub-groups as transudate (n:37) and exudate (n:84); and malignant (n:30) and non-malignant (n:91). Serum procalcitonin level of 0.035 was having a sensitivity of 0.726 and specificity of 0.964; on the other hand, pleural fluid procalcitonin level of 0.035 was having a sensitivity of 0.690 and specificity of 0.919. For serum procalcitonin /albumin ratio, 0.0104 value was having a sensitivity of 0.774 and specificity of 0.757 while for pleural fluid procalcitonin /albumin ratio of 0.019 value was having a sensitivity of 0.667 and specificity of 0.649. Conclusion: Serum and pleural fluid procalcitonin levels and procalcitonin/ albumin ratio were having a significant role in differentiating transudate and exudate. However, procalcitonin, CRP or any other ratios obtained from these parameters were not useful in diagnosis of malignant effusions.